2019
DOI: 10.1523/jneurosci.0305-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Network Activation of Hypothalamic MCH Neurons in REM Sleep and Exploratory Behavior

Abstract: Most brain neurons are active in waking, but hypothalamic neurons that synthesize the neuropeptide melanin-concentrating hormone (MCH) are claimed to be active only during sleep, particularly rapid eye movement (REM) sleep. Here we use deep-brain imaging to identify changes in fluorescence of the genetically encoded calcium (Ca 2ϩ ) indicator GCaMP6 in individual hypothalamic neurons that contain MCH. An in vitro electrophysiology study determined a strong relationship between depolarization and Ca 2ϩ fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 41 publications
3
53
0
Order By: Relevance
“…(2016) revealed that MCH neurons increase their activity upon novel object recognition. Moreover, single-MCH-neuron-resolution-based Ca 2+ imaging revealed a predominant activation of MCH neurons during REM sleep ( Blanco-Centurion et al., 2019 ), whereas in another study, it was reported that MCH neurons exhibited a more heterogenous response dependent on sleep cycles and a majority of neurons was activated during REM sleep, but minor proportions did not respond to changes in sleep state or some even became activated upon awakening ( Izawa et al., 2019 ). These heterogenous responses are also consistent with the molecular heterogeneity of MCH neurons revealed in our single-nuclei sequencing experiments.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) revealed that MCH neurons increase their activity upon novel object recognition. Moreover, single-MCH-neuron-resolution-based Ca 2+ imaging revealed a predominant activation of MCH neurons during REM sleep ( Blanco-Centurion et al., 2019 ), whereas in another study, it was reported that MCH neurons exhibited a more heterogenous response dependent on sleep cycles and a majority of neurons was activated during REM sleep, but minor proportions did not respond to changes in sleep state or some even became activated upon awakening ( Izawa et al., 2019 ). These heterogenous responses are also consistent with the molecular heterogeneity of MCH neurons revealed in our single-nuclei sequencing experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The high density of MCHR1 in the caudate‐putamen and its presence in the ventral tegmental area also allows MCH to act on reward circuits through the mesolimbic pathway (Domingos et al., 2013). Through the pyramidal layer of the hippocampus proper, MCH may act on learning, novelty, spatial and contextual memory retrieval, and anxiety (Blanco‐Centurion et al., 2019; Izawa et al., 2019; Jimenez et al., 2018; Monzon et al., 1999; Oh et al., 2019; Sita, Diniz, Canteras, Xavier, & Bittencourt, 2016), with important ramifications for animal behavior. The presence of ciliary MCHR1 on dopaminergic neurons of the incerto‐hypothalamic area may be the nexus for an MCH role on reproductive behavior and hormone secretion (Murray, Mercer, et al., 2000), while through tuberoinfundibular dopaminergic neurons it may interface with prolactin secretion (Hökfelt & Fuxe, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…The high density of MCHR1 in the caudate-putamen also allows MCH to act on reward circuits through the mesolimbic pathway (Domingos et al 2013). Through the pyramidal layer of the hippocampus proper, MCH may act on learning, novelty, spatial and contextual memory retrieval, and anxiety Monzon et al 1999;Blanco-Centurion et al 2019;Oh et al 2019;Jimenez et al 2018), with important ramifications for animal behavior. The presence of ciliary MCHR1 on dopaminergic neurons of the incerto-hypothalamic area may be the nexus for an MCH role on reproductive behavior and hormone secretion (Murray et al 2000a), while through tuberoinfundibular dopaminergic neurons it may interface with prolactin secretion (Hökfelt & Fuxe 1972).…”
Section: Discussionmentioning
confidence: 99%